Accumulation of Labile P Forms and Promotion of Microbial Community Diversity in Mollisol with Long-Term Manure Fertilization - Shuhui Song; Jinyao Zhang; Yunxia Liu; Hong Wang (Agronomy, 2023)
Soil phosphorus (P) can be divided into inorganic P (Pi) and organic P (Po). Microorganisms play essential roles in soil P transformation. However, there are many ways to detect P transformation, and the relationship between P forms and microorganisms under long-term fertilization is largely unclear. In this study, soil P forms were analyzed by a chemical sequential fractionation method and solution 31P nuclear magnetic resonance (31P-NMR) technique. Phospholipid fatty acid (PLFA) contents were measured by gas chromatography as the characterization of soil microbial community structures. The objective was to determine the changes of soil P forms and associated microbial community composition in mollisol with long-term fertilization. We sampled soil from a field experiment with 26-year-old continuous maize (Zea mays L.) cropping in Northeastern China. Three fertilization treatments were selected as chemical fertilization (NPK), NPK with crop straw (NPKS), and NPK with manure (NPKM). As shown in 31P-NMR spectra, orthophosphate accounted for 62.8–85.8% of total extract P. Comparison to NPK and NPKS treatments, NPKM application notably increased the concentrations of Po, Olsen-P, orthophosphate, orthophosphate monoester, and total P. Soil P fractions including resin-Pi, NaHCO3-P, NaOH-P, and HCl-P, especially Pi fractions, were enhanced by NPKM. The amounts of total PLFAs and PLFAs in bacteria, Gram-positive (G+) and Gram-negative (G−) bacteria, actinomycetes, and fungi were high in NPKM-treated soil. The percentages of PLFAs in bacteria and fungi in total soil PLFAs were 56.8% and 9.7%, respectively, which did not show any significant difference among the treatments. NPKM increased the proportions (%) of PLFAs in G+ bacteria, and NPKS increased the proportions (%) of G− bacteria in total PLFAs. The composition of soil microbial community was found to be significantly affected by soil total carbon and pH. There was a close relationship between HCl-Pi, NaHCO3-Po, orthophosphate, and pyrophosphate with anaerobe, aerobes, and G+. Manure addition directly increased soil available P concentrations, and indirectly acted through the alterations of anaerobe, aerobes, and G+. It is concluded that long-term NPKM application would lead to the accumulation of labile P and moderately labile P in mollisol through the activity of soil microbes.